2014
DOI: 10.1002/srin.201400207
|View full text |Cite
|
Sign up to set email alerts
|

Numerical, Physical, and Industrial Studies of Liquid Steel Chemical Homogenization in One Strand Tundish with Subflux Turbulence Controller

Abstract: Chemical homogenization of liquid steel is one of the basic parameters defining quality of final products. The 95% chemical homogenization level is a required minimum that defines the effective dissolution of all the components introduced to the liquid steel. The object of investigation was a one-strand wedge-type tundish designed for casting slabs. For the set zone of alloy feeding, numerical simulations, laboratory experiments (with a isothermal physical water model) and industrial experiments were carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…However, feeding alloy additions to liquid steel during the course of continuous casting at the tundish stage is limited by two basic factors, liquid steel temperature (20-30°C above liquidus temperature of heat) and the limited time of additional treatment of liquid steel in tundish (average residence time of liquid steel). The investigation results reported earlier confirmed that there were real grounds for developing a technology for efficient feeding alloy additions to liquid steel during continuous casting process [7][8][9]. The present study reports the results of investigation into the hydrodynamic pattern forming in the tundish and its effect on the time of alloy addition mixing with liquid steel.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, feeding alloy additions to liquid steel during the course of continuous casting at the tundish stage is limited by two basic factors, liquid steel temperature (20-30°C above liquidus temperature of heat) and the limited time of additional treatment of liquid steel in tundish (average residence time of liquid steel). The investigation results reported earlier confirmed that there were real grounds for developing a technology for efficient feeding alloy additions to liquid steel during continuous casting process [7][8][9]. The present study reports the results of investigation into the hydrodynamic pattern forming in the tundish and its effect on the time of alloy addition mixing with liquid steel.…”
Section: Introductionsupporting
confidence: 77%
“…1), are presented in Table 1. All of the proposed FCDs are described in detail in papers [7][8][9]. zone, the feeding stream is directed towards the upper liquid steel surface.…”
Section: Characterization Of the Test Facility And Computing Methodologymentioning
confidence: 99%
“…The next investigation stage included numerical simulations of the behavior of liquid steel under isothermal conditions for the proposed tundish furnishing variants. A detailed description of the hydrodynamic pattern occurring in the low‐dam tundish working space is provided in the work . Figure shows the stream lines and velocity vectors of liquid steel flow structures forming in the plane located through porous plug no.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the maximum cell volume equals 5.4 × 10 −5 m 3 . The numerical model and the physicochemical quantities for the liquid steel and argon are described in detail in the previous work . For describing the turbulence motion of liquid steel and argon, the realizable k–ϵ model was adopted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation